Electoral Incentives in Congress - Carson, Jamie L.; Sievert, Joel (Book collections on Project MUSE., 2018)
"David Mayhew's (1974) thesis regarding the "electoral connection" and its impact on legislative behavior has become the theoretical foundation for much of the existing research on the modern U.S. Congress. In its most basic form, Mayhew's theory contends that once in office, legislators pursue whatever actions put them in the best position to achieve reelection. The electoral connection has traditionally been considered a phenomenon of the post-World War II environment, but legislative scholars have begun to suggest that Mayhew's argument applies to politics in earlier congressional eras as well. To assess these disparate claims more systematically, Carson and Sievert investigate whether legislators in earlier historical eras were motivated by many of the same factors that influence their behavior today, especially with regard to the pursuit of reelection. In this respect, they examine the role of electoral incentives in shaping legislative behavior across a wide swath of the nineteenth century. This entails looking at patterns of turnover in Congress across this period, the politics underlying renomination of candidates, the changing role of parties in recruiting candidates to run and its broader effect on candidate competition, as well as electoral accountability across a variety of dimensions. The results have wide-ranging implications for the evolution of Congress and the development of various legislative institutions over time"--